2021
DOI: 10.1021/acs.iecr.1c03935
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Low-Polymeric VOx/Silica Gel Catalyst for Efficient Catalytic Dehydrogenation of Propane to Propylene

Abstract: Developing an efficient propane dehydrogenation (PDH) is a profound challenge for the production of propylene from the abundant source of propane in the chemical industry. In this work, a simple, efficient, and easy-to-operate process for highly selective PDH to propylene over low-polymeric VO x /silica gel (VO x /SG) catalyst has been successfully developed. The results demonstrate that the low-polymeric VO x /SG catalyst exhibits high selectivity (∼95%), good conversion (45.0 to 26.4% over 10 h test), and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The Raman spectrum of SSZ-13 zeolite was collected as a reference background. As exhibited in Figure , like SSZ-13 zeolite, no bands are observed for the 1V/SSZ catalyst in the range 200–1200 cm –1 , indicating that isolated VO 4 species are dominant. , Both 5V/SSZ and 12V/SSZ exhibit characterized Raman bands at 332, 480, and 1030 cm –1 , which are attributed to V–O–V stretching vibrations of polymerized VO X species, , V–O–V bending vibrations of polymerized VO X species, and VO stretching vibrations of the isolated and low-polymerized VO X species. ,, Compared to 5V/SSZ, the obvious increment in the intensity of all of the Raman bands for 12V/SSZ can be ascribed to the aggregation of more VO X species on the surface of SSZ-13 zeolite. , The absence of sharp band at approximately 990 cm –1 assigned to the VO stretching vibration of crystalline V 2 O 5 excludes the formation of bulk V 2 O 5 crystalline on all x V/SSZ catalysts. , This is consistent with the above XRD results, further proving the good dispersion of VO X species on the SSZ-13 zeolite surface.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The Raman spectrum of SSZ-13 zeolite was collected as a reference background. As exhibited in Figure , like SSZ-13 zeolite, no bands are observed for the 1V/SSZ catalyst in the range 200–1200 cm –1 , indicating that isolated VO 4 species are dominant. , Both 5V/SSZ and 12V/SSZ exhibit characterized Raman bands at 332, 480, and 1030 cm –1 , which are attributed to V–O–V stretching vibrations of polymerized VO X species, , V–O–V bending vibrations of polymerized VO X species, and VO stretching vibrations of the isolated and low-polymerized VO X species. ,, Compared to 5V/SSZ, the obvious increment in the intensity of all of the Raman bands for 12V/SSZ can be ascribed to the aggregation of more VO X species on the surface of SSZ-13 zeolite. , The absence of sharp band at approximately 990 cm –1 assigned to the VO stretching vibration of crystalline V 2 O 5 excludes the formation of bulk V 2 O 5 crystalline on all x V/SSZ catalysts. , This is consistent with the above XRD results, further proving the good dispersion of VO X species on the SSZ-13 zeolite surface.…”
Section: Resultsmentioning
confidence: 89%
“…15,28 Both 5V/SSZ and 12V/SSZ exhibit characterized Raman bands at 332, 480, and 1030 cm −1 , which are attributed to V−O−V stretching vibrations of polymerized VO X species, 17,29 V−O−V bending vibrations of polymerized VO X species, 30−32 and V�O stretching vibrations of the isolated and low-polymerized VO X species. 28,33,34 Compared to 5V/SSZ, the obvious increment in the intensity of all of the Raman bands for 12V/SSZ can be ascribed to the aggregation of more VO X species on the surface of SSZ-13 zeolite. 34,35 The absence of sharp band at approximately 990 cm −1 assigned to the V�O stretching vibration of crystalline V 2 O 5 excludes the formation of bulk V 2 O 5 crystalline on all xV/SSZ catalysts.…”
Section: Crystalline Phase Analysismentioning
confidence: 97%
“…[9][10][11][12] In addition, previous research has shown that a high dispersion of active species is beneficial for the production of ethylene, propylene, and oxygenates. [13][14][15] Meanwhile, V/SiO 2 has proven to be a promising catalyst for the selective oxidation of ethane or propane, maximizing the dispersion of the components and further promoting the activity and stability of the conversion of ethane or propane. [16,17] Mesoporous silica materials have numerous advantages, including high thermal stability and large pore entrances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a wide variety of non-noble metal materials such as Fe, Co, Ru, Rh, Zn, V, Ga, W, and Zr-based dehydrogenation catalysts also have been intensively explored, which exhibit excellent performance serving as promising candidates as catalysts for PDH, but still many problems are unsolved. 13–21…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a wide variety of nonnoble metal materials such as Fe, Co, Ru, Rh, Zn, V, Ga, W, and Zr-based dehydrogenation catalysts also have been intensively explored, which exhibit excellent performance serving as promising candidates as catalysts for PDH, but still many problems are unsolved. [13][14][15][16][17][18][19][20][21] In this review, a comprehensive overview of the research progress and future prospects for PDH catalysts will be given. Firstly, the recent advances in Pt-based, CrO x -based and other non-noble metal based PDH catalysis are summarized in categories.…”
Section: Introductionmentioning
confidence: 99%